Redesign of water filter using design for manufacturing and assembly to minimize cost and time - Ignadia Zain Balqis; Rusindiyanto Rusindiyanto; Endang Pudji Widjajati (Universitas Ahmad Dahlan, 2022)
Kembang Belor Village is one of the villages that have a water resource but are not yet precisely utilized and need a water filter. The current water filter is not suited for users’ needs because they cannot afford it. Therefore, this research intends to redesign the water filter. This research aims to reduce production costs and increase the efficiency of design and assembly time. The method employed is Design for Manufacturing and Assembly (DFMA). The results show that the production cost decreased by 50.83%; design efficiency increased by 37.5%; production, handling, and assembly time improved by 51.7%, 33.3%, and 52.7% for each; the number of ppm decreased from 142 to 95. For the contribution, few previous research uses the DFMA method to analyze and redesign the water filter. These findings contribute in helping the user recognize new options to design efficient water filters for future needs.